Effects of teaching style in the tagrugby unit on situational and contextual motivational variables - Jesús Otto Castrillo; Javier Sevil Serrano; Ángel Abós Catalán; Luis García-González (Federación Extremeña de Balonmano; University of Extremadura, 2016)
This study aims to evaluate the development of a teacher intervention in a didactic unit and to check their effect on different motivational variables at both situational and contextual levels. It proposed an intra-group study during a sequence of two didactic units in physical education (PE) in which 97 students took part (M = 13.64, DT = 0.75). A series of strategies connected with TARGET areas were applied solely in the tagrugby unit. Motivational climate and basic psychological needs support were measured at the end of the two units to check the effectiveness of the intervention. Furthermore, different motivational variables were measured before and after the intervention in the tagrugby unit. The results showed greater task climate and support of the basic psychological needs in the tagrugby unit. Moreover, greater values were shown in perception of autonomy, introjected regulation and affective attitude in PE lessons, after the intervention in the tagrugby unit. Therefore, the application of strategies based on the TARGET areas may be effective on different motivational variables, in both content and in PE classes.